e-TEP Retromuscular Repair for Recurrent Incisional Hernias: Report of Three Cases - Vikal Chandra Shakya; Bikram Byanjankar; Rabin Pandit; Anang Pangeni; Anir Ram Moh Shrestha (Case Reports in Surgery)
Introduction. Recurrent incisional hernias are difficult to treat. There are many factors involved in the recurrence, and due to extensive dissections, the planes are fused with adhesions, and we may need a new plane for dissection and placement of meshes. Case Report. We report here three cases of recurrent incisional hernias which were dealt by a relatively new method to laparoscopy: the enhanced view totally extraperitoneal repair (e-TEP) retromuscular technique. There were three patients: one after an open onlay repair of lower midline incision, another after an onlay mesh repair of a subcostal incision for open cholecystectomy followed by an intraperitoneal onlay mesh hernioplasty (IPOM) repair, and another after IPOM repair of epigastric hernia. They were treated with the abovementioned technique with satisfying short-term results. Conclusion. The e-TEP technique is a relatively new method of providing minimal access surgery to these patients utilizing the previously unaccessed retromuscular (Rives and/or preperitoneal) space for the repair of these recurrent incisional hernias.